Make it Real: The Clover is Ours - Forero Ruiz, Andrés Felipe (Instituto para la Investigación Educativa y el Desarrollo Pedagógico, IDEP, 2022)
The main subject of this essay is to present the project called Hágalo Real: el Trébol es Nuestro which is conducted as investigation framework in the research project named: Hágalo real Sistematización del proceso de creación colectiva de la Casa cultural el Trébol de Todos y Todas, en el barrio Ciudad de Cali, Bogotá. Paper presented as essential to accomplish the master’s degree in education of the National Pedagogic University of Colombia. The purpose of this plan is focused on developing a process of collective creation in fellowship regarding the same community who was part of the Cultural House El Trébol and the people who nowadays inhabit the same place. First, the historical context and the territory where the house is located, are described in the present paper. Besides, in the specific section, it is introduced the social house project: Ciudad Techo, The Corporation de Abastos de Bogotá (or Corabastos) and the creation of the barrio Ciudad de Cali as a historical milestone for the informal-sellers (Pirates) urbanization process of the southwestern area of the city. The second section briefly explains the history of the creation of the Casa Cultural el Trébol de Todos y Todas and lastly, in the third segment, it is described a current process, where there are three training activities, developed with different artists and community leaders within the background of this educational project.